Socio cultural perspective on a formation of peri-urban identity in Kuala Selangor Region, Malaysia - Mazlan, Maizura; Ismail, Nor Atiah; Abdul Aziz, Faziawati; Mohd Yusof, Mohd Johari (Science Publishing Corporation, 2019)
At present time, Malaysia gradually undergoes a pace of urban and rural transformation. The rapid growth of cities in Malaysia expanding beyond their incorporation boundaries transformed the land use from rural to urban. This situation developed an area in between urban and rural knows as peri-urban area which increase in number and typologies. Peri-urban continues to grow spatially and in population, thus these zones have unique identities which continue to evolve. Thus, the aim of this article is to explore the importance of socio-cultural landscape at Kuala Selangor as urban peripheries and how it could establish the identity for the future of a good environment.Providing a socio-cultural approach to the peri-urban notion, this paper discovers through the literature study the subjective dimension on the socio-cultural definition at the peri-urban area, in order to understand its ‘unique identity’. In this article, the notion of ‘socio-cultural landscape’ is presented in arrange to investigate the ambiguity that exists within these days peri-urban area with respect to their social and unique presence. The paper is based on an extensive literature review to distinguish the significance of socio-cultural landscape for peri-urban areas in regards to revive its image and identity.